Performance evaluation of AODV, DSR and DYMO routing protocol using NS2 / Mior Norazman Mior Daud - Mior Daud, Mior Norazman (2008)
A mobile ad-hoc network (MANET) is a kind of wireless ad-hoc network, and is a self-configuring network of mobile routers connected by wireless. MANET may operate in a standalone fashion, or may be connected to the larger Internet. Many routing protocols developed for MANETs over the past few years. This project was evaluate three of MANET routing protocols which are Ad-hoc On-demand Distance Vector (AODV), Dynamic Source Routing (DSR) and Dynamic MANET Ondemand routing protocol (DYMO) to make better understand the major characteristics of the three routing protocols. Different performance aspects were investigated in this project including, packet delivery ratio, routing overhead, throughput and average end to end delay. This project was use Linux as a operating system based platform and using a discrete event simulator NS2 as a simulation software to compare three MANET routing protocol. The NS2 is written in C++ and an Object oriented version of Tel called OTCL. This project simulation results indicated that all routing protocols perform well according to performance metrics that be selected. For packet delivery ratio metric, performance of AODV, DSR and DYMO routing protocols quite similar between each others. DSR perform low and stable normalized routing overhead than AODV and DYMO for normalized routing overhead metric. Besides that, DYMO routing protocol perform well than AODV and DSR routing protocol in term of throughput. Finally, for average end to end delay, DYMO and AODV perform well than DSR.